Pemahaman Hadis Al-Ghazali Tentang Menasihati Pemimpin: Studi Kasus Pejabat Negara di Indonesia - Rizqi Shohibul Khotami; M. Reza Saputra (Tabsyir: Jurnal Dakwah dan Sosial Humaniora, 2024)
This research examines Al-Ghazali's understanding of advising leaders and its relevance to the context of leadership in Indonesia. Employing a qualitative approach with a case study method, data was gathered through documentation of Al-Ghazali's works, case studies of corruption and ethical violations among Indonesian state officials, and in-depth interviews with experts in Islamic leadership, academics, and legal practitioners. The findings indicate that Al-Ghazali's teachings on character, integrity, and morality in leadership are highly relevant to addressing leadership challenges in Indonesia, such as corruption and abuse of power. Ulama (Islamic scholars) play a crucial role in advising leaders to enhance leadership quality and governance. This research also contributes theoretically to the study of Islamic leadership ethics, demonstrating that ethical principles derived from hadiths can develop an ethical and effective governance model in diverse cultural contexts. By implementing Al-Ghazali's leadership principles, it is hoped that more just, transparent, and people-oriented leadership can be established in Indonesia.